Effectiveness of Drug Supervisors in Increasing Tuberculosis Prevention Actions and Consumption of Tuberculosis Drugs - Irfan Irfan; Syaputra Artama; Aris Wawomeo (JURNAL INFO KESEHATAN, 2025)
National tuberculosis control continues to be carried out by intensification, acceleration, extensification and program innovation. One of the efforts with an effective Directly observed treatment shortcourse (DOTS) strategy. The main focus of this strategy is the discovery and cure of patients and breaking the chain of Tuberculosis transmission so as to reduce the incidence and increase Tuberculosis cure in the community. This research aimed to assess the efficacy of Drug Supervisors in reducing transmission and ensuring adherence to Tuberculosis medication throughout treatment. The study used a quasi-experimental design using a pre-posttest framework, comprising an intervention group of 14 participants and a control group of 14 participants. The group of subjects was observed before the intervention, namely direct supervision of taking medication (PMO) through the DOTS strategy by family/relatives/caregivers/officers on TB patients during the treatment period and observed again after the intervention. The sample was selected based on sub-district sample clusters using proportional allocation techniques. Bivariate analysis applied independent t test and mann whitney test (value α = 0.05) because the distribution of the data obtained was not normal. This research revealed that patients receiving intervention in the form of drug monitoring by PMO experienced an increase in TB transmission prevention measures higher than the control group, thus compliance in taking medication was higher in the case group compared to the control group (p 0.01). This indicates that a PMO is essential for every patient receiving Tuberculosis therapy to prevent lack of follow-up and mitigate the influence on the onset of TB-MDR.